Research and development for sustainable irrigation management - Lenton, R.L. (1994)
This paper seeks to provide guidelines to governments planning to undertake research and development programmes aimed at finding ways to manage irrigation systems in a sustainable way. After describing the challenges affecting irrigated agriculture at the present time, the paper presents two examples of action-oriented research projects, from which some preliminary principles for effective irrigation management research and development are derived.